2018
DOI: 10.1111/jvp.12712
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of danofloxacin in healthy andPasteurella multocidainfected ducks

Abstract: Pasteurella multocida (P. multocida) infection causes substantial economic loss in the duck industry. Danofloxacin, a fluoroquinolone solely used in animals, shows good antibacterial activity against P. multocida. In this study, the in vitro pharmacodynamics of danofloxacin against P. multocida was studied. The serum and lung tissue pharmacokinetics of danofloxacin were studied in healthy and P. multocida infected ducks following oral administration of a single dose of 5 mg/kg body weight (b.w.). The MIC, MBC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…In this study, the lower ClT/F of danofloxacin in the ID (0.38 L/h•kg) and IDM (0.28 L/h•kg) groups than that in the HD (0.45 L/h•kg) and HDM (0.32 L/h•kg) groups indicates the effect of infection. These findings are consistent with other studies that reported a reduced ClT/F of danofloxacin, marbofloxacin, and tilmicosin in respiratory infections [69][70][71][72]. However, the ClT/F of marbofloxacin increased in lambs naturally infected with M. haemolytica [73].…”
Section: Pharmacokinetics Of Danofloxacinsupporting
confidence: 92%
“…In this study, the lower ClT/F of danofloxacin in the ID (0.38 L/h•kg) and IDM (0.28 L/h•kg) groups than that in the HD (0.45 L/h•kg) and HDM (0.32 L/h•kg) groups indicates the effect of infection. These findings are consistent with other studies that reported a reduced ClT/F of danofloxacin, marbofloxacin, and tilmicosin in respiratory infections [69][70][71][72]. However, the ClT/F of marbofloxacin increased in lambs naturally infected with M. haemolytica [73].…”
Section: Pharmacokinetics Of Danofloxacinsupporting
confidence: 92%
“…Clinical symptoms and pathological changes were monitored using standard techniques. Bacteria isolated from liver and lung were cultured using MHA plates and identified by light microscopy after Wright–Giemsa staining to examine P. multocida as previously described (Xiao et al., ). The disease model was chosen when (a) animals showed the typical clinical symptoms and pathological changes; (b) P. multocida was isolated from liver and lung tissues; and (c) animals survived more than 36 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Consistently, the PK of danofloxacin in healthy and Pasteurella multocida infected ducks (both in serum and lung tissues) were different for both ducks (Xiao et al, ) and chickens (Zeng et al, ). The CL β / F was lower in infected ducks, and the T1/2β was also prolonged in infected animals, which means that the clearance and elimination rate of danofloxacin were slower in infected animals.…”
Section: Discussionmentioning
confidence: 81%
“…The CL β / F was lower in infected ducks, and the T1/2β was also prolonged in infected animals, which means that the clearance and elimination rate of danofloxacin were slower in infected animals. Besides, the total amount of drug (AUCs) in the circulation was increased in the Pasteurella multocida infected ducks, and the distribution rate of danofloxacin was slower in healthy ducks than in infected ducks (Xiao et al, ).…”
Section: Discussionmentioning
confidence: 99%